Production Uncertainty and the Heckscher-Ohlin Theorem - Batra, Raveendra N. (Review of Economic Studies, 1975)
Journal Article Production Uncertainty and the Heckscher-Ohlin Theorem Get access Raveendra N. Batra Raveendra N. Batra Southern Methodist University, Dallas Search for other works by this author on: Oxford Academic Google Scholar The Review of Economic Studies, Volume 42, Issue 2, April 1975, Pages 259–268, https://doi.org/10.2307/2296533 Published: 01 April 1975